Ezzat, Heba Raouf. “The Bitter Truth: Shaykh Muhammad al-Ghazali and Women's Issues," Year 2, Issue 7 (Winter 1416 AH/ 1997 CE), Pp. 87-104. - عزت, هبة رؤوف (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 1997)
The approach of Shaykh al-Ghazali is one of Islamic moderation. He confronted the enemies of Islam and those of corrupt religiosity. Heba Raouf Ezzat’s article narrates the life of Shaykh al-Ghazali, his upbringing, and his career. She further discusses al-Ghazali’s thought on women’s issues and his approach to the status of women and their functions in Muslim society, with reference to his book Qaḍāyā al-Mar’ah bayn al-Taqālīd al-Rākidah wa al-Wāfidah and his calls for a women’s rational Islamic renaissance that would treat the ills of the Ummah from an Islamic religious approach and not through secular Western solutions that only further corrupt and harm the Ummah. It also discusses al-Ghazali’s approach to the family and its position in human society and its role within the Islamic perspective in confronting contemporary challenges, whereby he puts emphasis on abiding by the bounds of conduct and Islamic moral values.